Memoria y ecos. Sobre Walter Benjamin - Vàzquez, Manuel E. (Bollettino Filosofico, 2016)
Analysis of the way that Walter Benjamin's philosophy goes from Berliner Chronik until Berliner Kindheit um Neunzehnhundert. The analysis takes into account the role of the city, politics and childhood, but fundamentally the role of memory and the passage in their understanding of a visual model to an acoustic model that articulates a coherent and novel way the relationship with the past.